Port resilience: a primer - Grainger, Andrew; Achuthan, Kamal (Dr Andrew Grainger, 2014)
The aim of this conceptual paper is to help stimulate further research and enquiry into UK Port Resilience and is a product of the EPSRC funded Knowledge Transfer Collaboration between the University of Nottingham and the Department for Transport (DfT). The paper draws on collaborative work between the authors and senior policy makers within the DfT, as well as on workshops, meetings and an extensive interview series with members of the UK’s port sector in order to address four key questions: